NURSING INTERVENTION IN PALLIATIVE CARE FOR PATIENTS WITH CHRONIC HEART FAILURE IN THE COMMUNITY - Rodríguez-León, Amarelys (2021)
In advanced stages of Heart Failure, drug therapy is not always effective and heart transplantation is not an option for all types of patients. In these conditions, palliative care arises as an alternative therapy to improve physical condition and quality of life. In order to design a nursing intervention in palliative care for patients with chronic heart failure in the community, a development research was carried out with a mixed approach of an explanatory sequential type, in the health area served by the Polyclinic XXX Anniversary of the Fall in Combat of the Heroic Guerrilla and his Companions, of the Remedios municipality, belonging to the province of Villa Clara, Cuba from 2018 to 2021. The patients with Chronic Heart Failure (CHF) of the referred Polyclinic and their relatives were taken into account to determine the population. The sample was made up of 158 patients by simple random probability sampling and 158 relatives by intentional non-probability sampling, with the inclusion criteria accepting to participate in the research. Symptoms of greater intensity were identified as edema in 63.29%, weakness and fatigue in 58.86%, cough in 51.26%, sweating and chest pain in 48.73%. Also, family care and communication needs. The Nursing Intervention designed for the integration of palliative care to patients with CHF, has a systemic and transformative approach, conceives the active role of the participants in the Intervention with group and personalized actions, which involves patients and their families, valued highly suitable by experts.